2019
DOI: 10.1007/s11069-019-03715-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial homogeneity of extreme precipitation indices using fuzzy clustering over northeast India

Abstract: Regionalization on the basis of the properties of hydro-meteorological data helps in identifying the regions reflecting the similar characteristics which could be useful in designing hydrological structures as well as planning and management of water resources of the region. In this study, rainfall data of northeast India were utilized for calculation of extreme precipitation indices as suggested by expert team on climate change detection and monitoring. Trend analysis of the indices was carried out using Mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…This study is consistent with the method used in our study to reflect changes in water quality factor concentrations through cluster analysis. In the precipitation study at Northeast India, Goyal, Shivam, and Sarma (2019) used fuzzy clustering to cluster the selected sites based on the six parameters of these precipitation indices, namely, latitude, longitude, mean, standard deviation, minimum and maximum (Goyal et al, 2019), and finally divided the sampling points into five categories for analysis, which is consistent with the method of classification analysis of sampling points in our paper. In the study of fuzzy clustering, Mao et al (2019) used the density centre as the initial cluster centre and finally developed a typical point selection method based on sampling density centre selection, which is consistent with our principles of fuzzy clustering in the study area and the selection of typical points based on the centre points of the clustering results.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This study is consistent with the method used in our study to reflect changes in water quality factor concentrations through cluster analysis. In the precipitation study at Northeast India, Goyal, Shivam, and Sarma (2019) used fuzzy clustering to cluster the selected sites based on the six parameters of these precipitation indices, namely, latitude, longitude, mean, standard deviation, minimum and maximum (Goyal et al, 2019), and finally divided the sampling points into five categories for analysis, which is consistent with the method of classification analysis of sampling points in our paper. In the study of fuzzy clustering, Mao et al (2019) used the density centre as the initial cluster centre and finally developed a typical point selection method based on sampling density centre selection, which is consistent with our principles of fuzzy clustering in the study area and the selection of typical points based on the centre points of the clustering results.…”
Section: Discussionsupporting
confidence: 59%
“…In the precipitation study at Northeast India, Goyal, Shivam, and Sarma (2019) used fuzzy clustering to cluster the selected sites based on the six parameters of F I G U R E 5 Food web structure level index changes of J1, J23, J24 and J32 (a-d represent J1, J23, J24 and J32, respectively, and the time is predicted based on the month of rainfall data collection. The red line in the figure is the mean line) these precipitation indices, namely, latitude, longitude, mean, standard deviation, minimum and maximum (Goyal et al, 2019), and finally divided the sampling points into five categories for analysis, which is consistent with the method of classification analysis of sampling points in our paper. In the study of fuzzy clustering, Mao et al (2019) used the density centre as the initial cluster centre and finally devel-…”
Section: Fuzzy Clustering To Determine Typical Pointsmentioning
confidence: 99%
“…3). Regionalization on the basis of the properties of hydro-meteorological data helps in identifying the regions re ecting the similar characteristics which could be useful in designing hydrological structures as well as planning and management of water resources of the region (Goyal et al, 2019). Clustering result showed relevance to the physiographic aspects that characterize the rainfall dynamics in CRJ.…”
Section: Resultsmentioning
confidence: 98%
“…Floods represent about one-third of all natural disasters. Together with storms they comprise 77% of economic losses caused by extreme weather events in Europe (Lechowska, 2018).The city of São Paulo, home to 11 million people, suffers constantly the effects of ooding caused by extreme precipitation Haddad and Teixeira (2015) estimated that oods contributed to reduce city growth and residents' welfare, as well as hampering local competitiveness in both domestic and international markets. An intra-city total impact-damage ratio of 2.2 and an economy-wide total impactdamage ratio of 5.0 were found.…”
Section: Resultsmentioning
confidence: 99%
“…Modarres (2006) and Ahmad et al (2013) respectively identified the homogeneous precipitation regions of Iran and Malaysia using a hierarchical clustering approach. Sahin and Cigizoglu (2010), Goyal et al 2019, andBasalirwa (1995) respectively in Turkey, India, and Uganda also applied clustering approaches for the same purpose. Furthermore, Abadi et al (2019) applied a multivariate clustering approach to divide Bolivia into identical and coherent climatological sub-regions.…”
Section: Introductionmentioning
confidence: 99%